2002
DOI: 10.1097/00002030-200203290-00008
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic or genotypic resistance testing for choosing antiretroviral therapy after treatment failure: a randomized trial

Abstract: Overall, resistance assays did not demonstrate benefit over standard of care. In patients with the most limited protease inhibitor experience, a significant benefit was observed in the genotyping arm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
164
3
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(174 citation statements)
references
References 22 publications
6
164
3
1
Order By: Relevance
“…Nevertheless, the advantage of genotyping information was lost after 12 months. These findings were similar to results from previous randomized studies [5][6][7][8][9], indicating that resistance testing helps to choose more effective regimens in patients failing previous antiretroviral regimens. Although group 2 patients had fewer mutations and viral samples with no mutations (wild type virus, Table 5), this group received less active drugs (Figure 2), thus emphasizing the importance of genotyping in salvage therapy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nevertheless, the advantage of genotyping information was lost after 12 months. These findings were similar to results from previous randomized studies [5][6][7][8][9], indicating that resistance testing helps to choose more effective regimens in patients failing previous antiretroviral regimens. Although group 2 patients had fewer mutations and viral samples with no mutations (wild type virus, Table 5), this group received less active drugs (Figure 2), thus emphasizing the importance of genotyping in salvage therapy.…”
Section: Discussionsupporting
confidence: 88%
“…Among others, the GART [6] and the NARVAL [7] studies demonstrated the usefulness of HIV genotyping, compared to phenotyping. The Argenta [8] and Havana [9] studies evaluated the effects of compliance and expert advice on HIV-1 genotyping.…”
mentioning
confidence: 99%
“…18,25,[30][31][32][33][34][35][36][37][38] Our analysis adds to several trials that have attempted to compare directly these two different methods. For the majority of these studies, the clinical outcomes have been similar regardless of the methodology: phenotype vs. virtual phenotype 39,40 and genotype vs. virtual phenotype; 33,41 however, in a subset of HIV-1-infected subjects with PI experience, a greater proportion of subjects achieved virologic suppression using genotypic testing vs. phenotypic testing 42 to guide antiviral selection. Although the optimum interpretation system has yet to be determined, our data suggest that the genotypic susceptibility scores perform similarly to the phenotypic susceptibility score in being correlated with virologic outcome.…”
Section: Comparison Of the Predictive Value Of Gss Versus Pssmentioning
confidence: 99%
“…Plasma HIV-1 RNA was <200 copies/mL at week 12 in 35% of patients in the phenotyping group, 44% in the genotyping group, and 36% in the standard-of-care group (phenotyping versus standard-of-care, P = 0.918; genotyping versus standard-of-care, P = 0.120). In a subset analysis of 179 patients experiencing a first protease inhibitor failure, the percentage of patients achieving HIV-1 RNA <200 copies/mL was significantly higher in the genotyping group (65%) than in the phenotyping (45%) and the standard-of-care groups (45%) (genotyping versus standard-of-care, P = 0.022) (13). Another study involving 450 participants failed to show that an overall improvement in the time to refractory treatment failure was associated with routine access to either genotype or phenotype resistance testing when used in a cohort of patients with a large number of enrollees with limited previous ART exposure (19).…”
Section: Discussionmentioning
confidence: 94%
“…Prospective studies have shown shortterm improvement in virus load suppression when genotype testing was used to guide therapy in naive and experienced patients (8)(9)(10)(11). Other recent studies have shown either transient improvement (12) or no benefit (13,14) associated with the use of genotype testing, i.e., resistance assays.…”
Section: Introductionmentioning
confidence: 99%